(untitled) (Biological Sciences - PJSIR, 2001)
Sixty three strains of Aspergillus niger were isolated and investigated for citric acid production. Three strains 5-43, 5-44 and 5-63 were found to produce citric acid with approximately 40% yield on thebasis of glucose or sucrose supplied. Media and carbohydrate concentrations were varied to optimize the citric acid production.